Human Defence Factors in Different Gestational Week Placenta: A Pilot Study - Andris Kamergrauzis; Mara Pilmane; Anna Junga (Life)
Background: Numerous studies have shown the presence of multiple defence factors in placental tissue, although their role is partially understood; therefore, the aim of this study was to evaluate the expression of nuclear factor-kappa B (NF-κB); human beta-defensin 2, 3, and 4 (HBD-2,3,4); cathelicidine (LL-37); heat shock protein 60 (HSP60); and interleukin 10 (IL-10) in dissimilar gestational week placental tissue and display correlations between immunoreactive cells. Methods: A total of 15 human placental tissue samples were acquired from mothers with different gestational weeks: 28, 31, and 40. Routine staining and immunohistochemistry for the samples were executed. The evaluation of data was performed with semi-quantitative methods, and, for statistical analysis, the Kruskal–Wallis test was used. Spearman’s rank correlation was used for calculating correlations. Results: NF-κB, HBD- 2,3,4, HSP60, and IL-10 expression were discovered in every examined placental tissue cell type. LL-37 expression was found only in Hofbauer cells. A rise in expression with higher gestational weeks was noted in LL-37-positive Hofbauer cells (p = 0.03), HBD-3-positive cytotrophoblasts (p = 0.007), endothelial cells (p = 0.024), extraembryonic mesodermal cells (p = 0.004), and HBD-4-positive endothelial cells (p = 0.001). Numerous statistically significant moderate and strong positive correlations between defence factors were discovered. Conclusions: The persistence of Hofbauer cell accumulations underlines the growing significance of placental macrophages in placental protection. The expression of positive defence factors and a rise in expression in tissue protection factors (HBD-3, LL-37, HBD-4) in higher gestational weeks may indicate these factors as the most significant protectors of the placenta in ontogenetic aspects. The high number of statistically significant positive and negative correlations between positive cells show a strong network to sustain distressed placental growth and therefore pregnancy.